Psikologi Pendidikan Anak (Pentingnya Peran Orangtua dalam Tumbuh Kembang Pendidikan Anak) - Nia Yunia Sari (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Abstract The idealism of being a successful parent, namely having children who are knowledgeable, faithful, obedient to their parents, beneficial to the nation and religion seems to be an obsession that is very difficult to realize.One of the basic rights of children is the right to grow and develop in all aspects of their lives, including the aspect of getting a proper education.This means that children have the opportunity to learn and gain knowledge as much as possible.This will all happen if the environment is very conducive so as to allow the development of children's education to be achieved optimally. But it's a shame, in this era, the development of children's education seems to be experiencing difficulties that are so transparent.The reality of environmental influences is already so strong,technology seems to poison the child's subconscious that learning is not fun. Plusthe influence of covid 19 which seems to have no end forcing children to study online which of course will have very low results.This problem is very disturbing for parents.The idealism of being a successful parent by having educated children is an obsession that is difficult to realize at this time.At this stage, the role of parents is very important in an effort to support the growth and development of children's education.It is important for parents to understand the growth and development of children's education.However, problems often arise when parents do not realize how important the presence of parents in the education of their children is.Parents seem to give up their hands by completely handing over their children's education to schools and teachers. This article uses a type of library research. This research was conducted to collect and analyze data sourced from books, magazines, newspapers and other scientific works.library research using a qualitative descriptive approach.Based on the results of various studies are presented to discuss various problems that are currently being faced. The indication of the results of this study is the lack of awareness of parents to understand the nature of their responsibilities and their role in efforts to encourage the development of children's education.Not all family environments can meet the expectations and needs of children, especially in their development and education.A family environment that acts as a good educator and meets standards is a must, especially for parents.f not, then the stakes are the child's development. Because parents and children work together to support their children's future.